Flexible graphene-coated carbon fiber veil/polydimethylsiloxane mats as electrothermal materials with rapid responsiveness - Zhang, XuFeng; Li, Dihui; Liu, Kejian; Tong, Jianfeng; Yi, XiaoSu (KeAi Communications Co., Ltd., 2019)
Flexible electrothermal mats with rapid responsiveness were prepared by spray-coating of graphene nanoplates (GNP) acetone dispersion on carbon fiber veil and following curing of polydimethylsiloxane (PDMS) on the mats. Morphological feature, electrical property, and electrothermal behavior of the mats with different area density from 55 to 20 g m−2 were investigated. Scanning electronic microscope (SEM) confirmed that pristine graphene nanoplates were uniformly deposited on the surface of carbon fiber resulting in volume resistance decreased substantially. Compared with the carbon fiber veil without coated GNP, the electric heating behavior of graphene-coated carbon fiber/PDMS mats were improved largely, such as the stead-state maximum temperature reached 297 °C, the maximum heating rate reached 5°Cs−1 tested by an infrared camera, the maximum power density reached 11.11 kW m−2. The respond time from room temperature 25 °C–200 °C was only 40 s tested by infrared thermal image. Even under high twisting/bending state or continuous stepwise voltage changes, the graphene-coated carbon fiber/PDMS mats retained stable electrical heating performance in aspects of temperature responsiveness and steady-state maximum temperature.